SPEECH DISORDERS AND THEIR CORRECTION IN POST-STROKE PATIENTS - O. V. Kurushina; A. E. Barulin; E. A. Kurakova; H. Sh. Ansarov (Медицинский совет, 2017)
The article is dedicated to the diagnosis, classification, and rehabilitation of various forms of speech disorders in poststroke patients. It is considered the most common types of expressive and impressive speech disorders. The main diagnostic signs of most frequent forms of aphasia and dysarthria are given. A plan for the rehabilitation program with the inclusion of a medication (Ceraxon®) and non-pharmacological methods of correcting speech disorders after stroke is offered.